Determining progression of scleroderma-related interstitial lung disease. Issue 1 (February 2019) - Volkmann, Elizabeth R; Tashkin, Donald P; Sim, Myung; Kim, Grace Hyun; Goldin, Jonathan; Clements, Philip J
Interstitial lung disease occurs in the majority of patients with systemic sclerosis. Although interstitial lung disease is the number one cause of death in systemic sclerosis, interstitial lung disease progression rates vary considerably among patients with systemic sclerosis. Some patients with systemic sclerosis–associated interstitial lung disease have sub-clinical disease and may not derive benefit from immunosuppression, while others have a more aggressive interstitial lung disease phenotype. Reliable predictors of interstitial lung disease progression are lacking. The present review describes our current approach to monitoring systemic sclerosis–associated interstitial lung disease progression in clinical practice. To illustrate the marked heterogeneity that exists in interstitial lung disease progression rates in systemic sclerosis, this review presents the individual disease course of five unique patients with systemic sclerosis–associated interstitial lung disease who participated in the Scleroderma Lung Study II. These cases illustrate that treatment response rates vary in systemic sclerosis–associated interstitial lung disease and more research is needed to determine how to predict treatment response in systemic sclerosis–associated interstitial lung disease and to develop personalized treatment approaches for patients with this devastating disease.